Generalized Model and Optimal Solution of Internet Pricing Scheme in Single Link under Multiservice Networks - Irmeilyana Irmeilyana (ICON-CSE, 2014)
In this paper, we will analyze the internet pricing scheme under multi service network by generalizing the model into 9 services. The scheme is determined from the base price, quality premium and number of links to aid the internet service provider to maximize the profit and to serve better service to the customers. The objective function is generated by setting up the base price and quality premium as a constant or variable. We use nonlinear optimization model and solve it by using LINGO 11.0 to obtain the optimal solution. The results show that for each case by generalizing the model, the ISP obtains better solution by fixing the base price and fixing and varying the quality premium. ISP has a choice to adopt the model when ISP fixes the base price and also fix or vary the quality premium with maximum profit adopted by ISP is when fixing the base price and varying the premium quality.